Blood volume: importance and adaptations to exercise training, environmental stresses, and trauma/sickness - Sawka, M. N.; Convertino, V. A.; Eichner, E. R.; Schnieder, S. M.; Young, A. J. (Medicine & Science in Sports & Exercise, 2000)
This paper reviews the influence of several perturbations (physical exercise, heat stress, terrestrial altitude, microgravity, and trauma/sickness) on adaptations of blood volume (BV), erythrocyte volume (EV), and plasma volume (PV). Exercise training can induce BV expansion: PV expansion usually occurs immediately, but EV expansion takes weeks. EV and PV expansion contribute to aerobic power improvements associated with exercise training. Repeated heat exposure induces PV expansion but does not alter EV. PV expansion does not improve thermoregulation, but EV expansion improves thermoregulation during exercise in the heat. Dehydration decreases PV (and increases plasma tonicity) which elevates heat strain and reduces exercise performance. High altitude exposure causes rapid (hours) plasma loss. During initial weeks at altitude, EV is unaffected, but a gradual expansion occurs with extended acclimatization. BV adjustments contribute, but are not key, to altitude acclimatization. Microgravity decreases PV and EV which contribute to orthostatic intolerance and decreased exercise capacity in astronauts. PV decreases may result from lower set points for total body water and central venous pressure, while EV decreases may result from increased erythrocyte destruction. Trauma, renal disease, and chronic diseases cause anemia from hemorrhage and immune activation which suppresses erythropoiesis. The re-establishment of EV is associated with healing, improved life quality, and exercise capabilities for these injured/sick persons.